A conceptual model of assessment of knowledge transfer to consumer - Raudeliūnienė, Jurgita; Davidavičius, Sigitas (Business, Management and Economics Engineering, 2017)
Due to changing needs of knowledge consumers in the context of globalization organizations find it important to search out the way of effective application of the process of knowledge sharing and distribution in their activity in order to create and/or select proper means of communication with consumers on purpose of effective satisfaction of their knowledge needs. In order to address the problems of such nature it is important to assess the process of knowledge transfer and consumer purchase, knowledge needs, knowledge transferred to meet of consumer needs, channels and means of knowledge transfer. Also, to select purposefully channels of communication with consumers and tools of e-marketing that are suitable for satisfaction of consumer needs, i.e. channels and tools that affect self-determination of consumer to take a decision to acquire a product or service of specific organization.